Socio economic impact of undeclared blockade of India on Nepal (Research Nepal Journal of Development Studies, 2018)
Indian unofficial or undeclared blocked was a terrible move. It was a move on the part of Indian diplomacy. India imposed it, it was very transparent but not acceptable. Diplomacy is getting thing done without speaking or telling nastiest words in nicest manner. What had happened in southern border of Nepal? What was Indian's role? The study attempts to find out the reason of undeclared blocked of 2015 and identify the socio economic impact of this blocked imposed during the dark days of great earthquake in Nepal. Can a neighbor do so? India did it but did not speak a single word. The study has been conducted to analyze the impacts of the issue. Library method and comparative review methods were applied to analyze the impacts it had on Nepal. They tried to minimize the Chinese Communists influences but the move was wrong. So, Nepalese citizens cast their vote to elect communist parties with full majority. Indian policy was concentrated on causing instability in Nepal. Nepalese diplomacy proved to be ineffective to put pressure on Indian government for amending the Sugauli Treaty and the Treaty of 1950 as well as addressing controversy over Kalapani, Susta and Lipulek. At the time of election, all the political parties raised the issue against India as KP Oli did and successfully won the election. The pain of blockade is not forgotten in the name of improving bilateral relations.Research Nepal Journal of Development Studies Vol.1(1) 2018 18-27